2020
DOI: 10.1038/s41598-020-73097-x
|View full text |Cite
|
Sign up to set email alerts
|

Turning date palm waste into carbon nanodots and nano zerovalent iron composites for excellent removal of methylthioninium chloride from water

Abstract: Novel carbon nanodots (nCD-DBC) and nano zero-valent iron composites (nZVI-DBC) were synthesized using date palm waste-derived biochar (DBC). The synthesized materials were analyzed for chemical and structural composition by using FTIR, SEM, XRD, and TGA, and evaluated for their methylthioninium chloride dye (MB) removal efficiency from contaminated aqueous solutions. pH 7.0 was found optimum for the highest MB removal in sorption batch studies. Kinetics sorption of MB onto the sorbents was best described by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…The speed constants predicted by the Elovich model were the highest (0.352 and 0.351 mg g −1 min −1 at pH = 6 and 9, respectively). This parameter defines the time the chemical process requires to complete [69]. The q e values estimated with the pseudosecond-order model were similar to the results from the experimental q e .…”
Section: Adsorption Isothermssupporting
confidence: 76%
“…The speed constants predicted by the Elovich model were the highest (0.352 and 0.351 mg g −1 min −1 at pH = 6 and 9, respectively). This parameter defines the time the chemical process requires to complete [69]. The q e values estimated with the pseudosecond-order model were similar to the results from the experimental q e .…”
Section: Adsorption Isothermssupporting
confidence: 76%
“…It was observed that mellite disappeared in the CBC and CBC-Fe due to composite formation ( Ahmad et al, 2019b ). The peaks regarding SiO 2 , turbostratic carbon, and graphite carbon were seen in the XRD pattern of CW, BC, and CBC, while these were absent in the CBC-Fe beads ( Ahmad et al, 2020 ). The FTIR spectra of the produced adsorptive materials before and after STZ removal were generated for this study.…”
Section: Discussionmentioning
confidence: 99%
“…49 Various microorganisms, such as bacteria, fungi, algae, and yeasts, have been employed to decolorize and degrade synthetic dyes. 39 Factors affecting the bioremediation and its mechanism Bioremediation methods for the removal of dyes can be carried out by the use of microorganisms (bacteria, fungi, algae, etc.) for the degradation of pollutants.…”
Section: Biological Methods For Degradation Of Dyesmentioning
confidence: 99%
“…At an optimal pH of 7.0, the results showed that nCD-DBC achieved 83% of decolorization of MB dye and nZVI-DBC showed a 38% removal. 39 Genetic engineering for the degradation of dyes Several microbiologists and molecular biologists have realized the scope of genetic engineering for biodegradation treatment. 117 Genetically engineered microorganisms (GEM), or genetically modified microorganisms (GMM), are modified by genetic modification techniques inspired by the natural genetic exchange between microorganisms and have served as an effective tool for biodegradation.…”
Section: Nanomaterials In Bioremediationmentioning
confidence: 99%